2021
DOI: 10.1111/jfbc.13650
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity effect of Brassica juncea cultivated in Jeongseon with optimized sinigrin content using 3T3‐L1 adipocytes

Abstract: Hee-Yeon Kwon and Sun-Il Choi contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…PPAR-γ, C/EBP-α, and ap2 are crucial factors in the transformation of preadipocytes into fully developed adipocytes [ 37 ]. In a previous study, BJE was reported to inhibit lipid accumulation by downregulating protein levels of PPAR-γ, C/EBP-α, and ap2, aligning with the findings of the current study [ 30 ]. ACC regulates the condensation of lipids and is integral in the overall regulation of energy metabolism [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…PPAR-γ, C/EBP-α, and ap2 are crucial factors in the transformation of preadipocytes into fully developed adipocytes [ 37 ]. In a previous study, BJE was reported to inhibit lipid accumulation by downregulating protein levels of PPAR-γ, C/EBP-α, and ap2, aligning with the findings of the current study [ 30 ]. ACC regulates the condensation of lipids and is integral in the overall regulation of energy metabolism [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, many studies have aimed to verify the efficacy of natural substances in functional foods and anti-obesity drugs, with the intention of reducing the various side effects associated with commercially available anti-obesity drugs [ 34 , 35 , 36 ]. This research was conducted to confirm the in vivo anti-obesity effect in an animal model, expanding on the results of prior in vitro investigations on the inhibition of lipid accumulation by BJE with an optimized sinigrin content [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations